Ludwig van Beethoven bust by Ludwig Albrecht for the 50th anniversary of the death of the great composer 26 March - Albrecht, Ludwig (artist):::Creator::::::::::::; Dietrich, Anton, 1833-1904 (sculptor):::Contributor::::::::::::; Lossow, A. (artist):::Contributor:::::::::::: (J.J. Weber; Leipzig; Germany)
Engraving of a Beethoven bust printed on the cover of the Illustrirte Zeitung (Leipzig) on March 24, 1877 (Band XLVIII, Nr. 1760). The bust depicted could be based on Anton Dietrich's bust of Beethoven located at the Opera of Vienna, or the bust of Beethoven by A. Lossow located at the Walhalla memorial in Regensburg.